Sintering Applications - Ertuğ, Burcu (IntechOpen, 2013)
Sintering is one of the final stages of ceramics fabrication and is used to increase the strength of the compacted material. In the Sintering of Ceramics section, the fabrication of electronic ceramics and glass-ceramics were presented. Especially dielectric properties were focused on. In other chapters, sintering behaviour of ceramic tiles and nano-alumina were investigated. Apart from oxides, the sintering of non-oxide ceramics was examined. Sintering the metals in a controlled atmosphere furnace aims to bond the particles together metallurgically. In the Sintering of Metals section, two sections dealt with copper containing structures. The sintering of titanium alloys is another topic focused in this section. The chapter on lead and zinc covers the sintering in the field of extractive metallurgy. Finally two more chapter focus on the basics of sintering,i.e viscous flow and spark plasma sintering.